2011
DOI: 10.5130/ajceb.v11i1.1660
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of Housing Demolition Decision Making and the Impact on Timber Waste Management

Abstract: The study investigates housing demolition and timber waste recovery -with the aim to identify ways of improving recovery. Using case studies the research focused on demolisher decision making, their onsite processes and the associated network of participants that influence timber recovery. From the data, a process model was developed that identifies and orders the drivers of demolition decision making. One aspect of the model identified the initiators of demolition and the waste created, including issues revol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Deconstruction faces economic barriers because it is more expensive than demolition, demanding more time and labour to recover comparably low-cost construction materials [44]. Several authors have argued that the low cost of construction materials compared to recovered/recycled materials is the problem in the cases of De and the 3Rs [43]. Moreover, the standard construction and demolition practices are focused on the fastest and most economical way to finish the job in the case of the 3Rs [44].…”
Section: Economic Barriersmentioning
confidence: 99%
See 2 more Smart Citations
“…Deconstruction faces economic barriers because it is more expensive than demolition, demanding more time and labour to recover comparably low-cost construction materials [44]. Several authors have argued that the low cost of construction materials compared to recovered/recycled materials is the problem in the cases of De and the 3Rs [43]. Moreover, the standard construction and demolition practices are focused on the fastest and most economical way to finish the job in the case of the 3Rs [44].…”
Section: Economic Barriersmentioning
confidence: 99%
“…Some authors reported the lack of tools for designers that would otherwise enable efficient deconstruction [25,37,52,58], help with assessing DW generation [30,55,66], promote the inclusion of new techniques for construction [44,46,61], and help with assessing the costs associated with IFD buildings [48]. Lastly, techniques for reusing reclaimed materials are also missing [25,37,43,48]. Meanwhile, down-cycling cannot be regarded as a closedloop (CL) approach because of the excessive loss of material value [62].…”
Section: Technology-related Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Forsythe [52] conducted a study on housing demolition and timber waste recovery in Australia and showed that demolishers' decision-making influences a number of aspects such as site safety, productivity, economic of scale, market value, and supply chain entrepreneurship. In addition, the project specific drivers including recurring cost versus income equates those impacts on the viability of project level decisions.…”
Section: The Key Challenges and Barriers Of Building Deconstructionmentioning
confidence: 99%
“…Forsythe [49] conducted a study on housing demolition and timber waste recovery in Australia and showed that demolishers' decision making influences a number of aspects such as site safety, productivity, economic of scale, market value and supply chain entrepreneurship. In addition, the project specific drivers including recurring cost versus income equation those impacts on the viability of project level decisions.…”
Section: The Key Challenges and Barriers Of Building Deconstructionmentioning
confidence: 99%